2014
DOI: 10.1074/jbc.m114.575183
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated Isocitrate Dehydrogenase 1 (IDH1) R132H Mutation and d-2-Hydroxyglutarate Stimulate Glutamine Metabolism under Hypoxia

Abstract: Background: Somatic IDH1 mutations are common in several types of cancer. Results: IDH1 mutation increases the proportion of palmitate derived from [13 C]glutamine under hypoxic conditions. Conclusion: IDH1 mutation can stimulate tumor cell reductive glutamine metabolism. Significance: IDH1 mutation may cause the unique glutamine-dependent metabolic phenotype observed in tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 33 publications
1
73
0
1
Order By: Relevance
“…Jaisson et al (2009) have shown that the mono γ-methyl ester of α-ketoglutarate is also an excellent substrate of mouse ω-amidase (Kranendijk et al 2010 and references cited therein). It is of considerable interest that many cancers carry a mutation in cytosolic NADP + -dependent isocitrate dehydrogenase that results in a gain-of-function, such that the enzyme catalyzes the non-physiological conversion of α-ketoglutarate to d-HG (e.g., Reitman et al 2014;Rakheja et al 2015).…”
Section: Possible Role Of ω-Amidase As a Repair Enzymementioning
confidence: 99%
“…Jaisson et al (2009) have shown that the mono γ-methyl ester of α-ketoglutarate is also an excellent substrate of mouse ω-amidase (Kranendijk et al 2010 and references cited therein). It is of considerable interest that many cancers carry a mutation in cytosolic NADP + -dependent isocitrate dehydrogenase that results in a gain-of-function, such that the enzyme catalyzes the non-physiological conversion of α-ketoglutarate to d-HG (e.g., Reitman et al 2014;Rakheja et al 2015).…”
Section: Possible Role Of ω-Amidase As a Repair Enzymementioning
confidence: 99%
“…Therefore, the present study has provided additional evidence for the reductive carboxylation pathway (17,18), which has recently become somewhat controversial (38). It was shown recently that isotopic labeling in citrate can occur from glutamine through isotopic exchange without net flux through the reductive pathway (39). This could be due to the reversibility of all the metabolic steps between ␣-ketoglutarate and citrate (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Glutamine can contribute to 2-HG synthesis through conversion to ␣-KG, via glutaminase (GLS-1) and glutamate dehydrogenase in cancer cells (20,28,32). Therefore, we next evaluated this pathway in our PKD model.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of 2-HG overproduction in cancer has been linked to mutant IDH1 or -2 in cancer, producing 2-HG from glutamine-derived ␣-KG and resulting in an increased flux through the glutamine pathway (20,28). However, 2-HG was also found to aberrantly accumulate in 1) breast cancer with c-Myc overexpression (28); 2) mutations in the genes encoding the D-2-hydroxyglutarate dehydrogenase (D2HGDH) and phosphoglycerate dehydrogenase (PHGDH) enzymes (5,25); and 3) hypoxic cancer cells due to increased levels of WT IDH2 and glutamine-sourced citrate (32).…”
Section: Resultsmentioning
confidence: 99%